The way of the Silver Age zoologist: practices of field work, capturing and collecting material - Igor Zagorodniuk (Geo&Bio, 2023)
The article is an essay on the formation and development of professional zoological research in Ukraine, with a focus on the study of terrestrial vertebrates, especially mammals, in particular during long-distance and long-term expeditionary trips and under conditions of stationary field research at biological stations. The heyday of such research is equated to the well-known renaissance of cultural processes of the late 19th and first third of the 20th century, but in field zoology such processes continued throughout the second third of the 20th century. The key features of the zoologists and field zoology of the Silver Age were constant (in fact, year-round) route excursions around the vicinity of large cities or various types of biological stations, as well as long-distance wagon-type collective expeditions, constant presence in nature with a gun more than with any type of trap, high specialisation on objects that could be obtained by shooting and were not small-sized and generally traditional hunting targets, linking the objectives of expeditions to material collection more than to observations (and, in fact, feedback, i.e. justification of expedition goals by the needs of collections accumulation). Special attention is paid to the traditional methods and volumes of material collecting. The changes in the practices of large expeditions and the factors of their extinction are considered. In particular, the latter is associated not so much with the disappearance of the need for material as with changes in the tasks of its analysis and the emergence of alternative, primarily live methods of studying certain species, as well as a departure from paradigmatic guidelines for describing and analysing the biotic diversity of regions and revising the taxonomy of groups and studying species variability using traditional systems of features, criteria, and approaches. The article analyses the value of the samples collected during the Silver Age and the tasks, motives and sources of enriching modern collections after the loss of the classical system of mass collection of morphological material.